Trần Thị Loan
17 tháng 10 2015 lúc 15:47

Từ 2.(x + y)= 5(y + z) = 3(z + x) => \(\frac{2\left(x+y\right)}{30}=\frac{5\left(y+z\right)}{30}=\frac{3\left(z+x\right)}{30}\) => \(\frac{x+y}{15}=\frac{y+z}{6}=\frac{z+x}{10}\)

Áp dụng t/c của dãy tỉ số bằng nhau ta có: \(\frac{x+y}{15}=\frac{y+z}{6}=\frac{z+x}{10}=\frac{\left(x+z\right)-\left(y+z\right)}{10-6}=\frac{\left(x+y\right)-\left(z+x\right)}{15-10}\)

=> \(\frac{x-y}{4}=\frac{y-z}{5}\) => \(\frac{x-y}{y-z}=\frac{4}{5}\)

Vậy...

Bình luận (0)

Các câu hỏi tương tự

Khoá học trên OLM của Đại học Sư phạm HN

Loading...

Khoá học trên OLM của Đại học Sư phạm HN